Jogo empresarial em ambiente virtual diferenças no processo de treinamento empresarial - Santander, Marli Teresa Jordan (2012)
Today we have corporate training that priority is develop competence necessary to performance of each function. Since the beginnings, games are used for many purposes and also today it can be used with that purpose. So, the objective of this research is check out if the insertion of games in on-line training can stimulate the players to realize the skills included in the game and enable a move to daily practice. Initially, the work bring a brief historical about School and Corporate Education, so as to demonstrate the evolution to a continuous education along the life in this two sectors. Last, share experience of a group of people in an on-line game to make collection of information. The development of this work was founded in a search of qualitative character with case study, because realization happened inside of on-line universe, with a group of people going through the experience in the game "Indiana Jones". An analysis and compilation of information gave possibility of conclude that the players are able to perceive competence that exist in the games when stimulated by directed questions